Safety Instructions through AI: A Case Study of Unforgettable Supporters Display in Sports Stadiums - Tarrence Karmelia Kontessa (Green Publisher, 2026)
Clear information about evacuation procedures in case of emergency will make spectators feel safe and comfortable during the event. However, in reality, such safety features are still rarely found in sports events in stadiums, especially in Indonesia “Unforgotten Supporters